Giant hydatid lung cyst in non-endemic area - E. Bindi; F. Nino; A. Simonini; G. Cobellis (Elsevier, 2021)
Echinococcosis is a parasitic zoonosis in which humans are involved as an intermediate host. It is a very common pathology in the areas of Eastern Europe and Asia, where the main activity is represented by pastoralism and animal breeding. In humans, the most frequently affected sites are the liver (60-70%) and lungs (20-30%), manifesting themselves with symptoms such as abdominal pain, coughing, dyspnea, hemoptysis, up to cases of anaphylactic shock. In Italy it is not a common disease with an incidence of 2:100.000 inhabitants, and it's extremely rare in pediatric population. In this work we presented a case of a 11-years male patient came for a persistent cough, to whom was found a giant cystic mass in the thorax. Serological tests confirmed the diagnosis of echinococcosis. Patient underwent to thoracotomy to remove the cyst and he begun the antiparasitic therapy. Post-operative outcome was good and the patient is, until now, free of problems. Echinococcosis is a challenging problem for a pediatric surgeon, especially in non-endemic area, not only because it is not a common disease in pediatric population, but also for the surgical management that can presents some difficulties and complications in the post-operative course.